Varieties of Verbal Doubling in Romance - Saab, Andrés Leandro (2017)
Recent research on verbal doubling across languages (Nunes 2004, Martins 2007,Kandybowicz 2009, Biberauer 2009, among others) shows that this phenomenon is afruitful domain of inquiry, especially regarding the nature of copying phenomena and the way in which such phenomena interact with syntax and morphology. In line with the aforementioned works, I focus on the empirical domain of verbal doubling in Spanish and European Portuguese and argue that not all verbal doublings are the result of syntactic copying. In particular, new evidence is discussed in order to show that predicate fronting in Spanish does not result from copying the overt lower predicate (pace Vicente 2007, 2009). Other varieties of verbal duplication, such as non-local doublings in Rioplatense Spanish and Italian, and local doublings in European Portuguese, are instead the direct result of verbal copy pronunciation arising from complex factors involving the structure of remnant movement and the general conditions that regulate copy pronunciation in syntax and morphology.